Designing the Appearance of a Telepresence Robot, M4K: A Case Study - Lee, Hyelip; Kim, Yeon-Ho; Lee, Kwang-ku; Yoon, Dae-Keun; You, Bum-Jae (CULTURAL ROBOTICS, CR 2015, 2016)
This paper presents the process for designing a telepresence robot (TPR) - M4K (Mobile 4-Dimensional Communication Kiosk), which offers more extensive interaction between users than other existing TPRs. The TPR is a robotic movable platform which helps people communicate across distances, and it is sometimes required to have the ability of 'tele-manipulation', which exceeds the current capacity of pure 'telecommunication' [13]. Of note, our M4K has an interactive 3D beam projector and cameras in addition to the basic TPR platform. The design process to give the M4K an acceptable form to users is presented. Following illustrating the design process, limitations and future works are discussed. The design process progresses from related research, ideal version design, to manufactured version design. This project is ongoing and at an estimated midway point of the whole development cycle, so it is also treated partly as an experiment. This study will be used to support the next phase of design and technical development.